A new species of the genus Eustigmaeus (Trombidiformes: Prostigmata: Stigmaeidae) and the first record of E. extremiorientalis in Japan - Ikeda, Satsuki; Imada, Yume; Nakano, Takafumi (Zootaxa, 2024)
A new stigmaeid mite species Eustigmaeus imadae sp. nov. (Trombidiformes: Prostigmata: Stigmaeidae) is described from Japan. The species was collected from Shikoku and Honshu Islands. Insights into morphological variation among the specimens collected from different localities are provided. Eustigmaeus extremiorientalis Khaustov, 2016 originally described from Russia is recorded for the first time in Japan and is described based on specimens from the Japanese population. The number of Eustigmaeus species known in Japan has now increased to six.